Factors associated with home hazards: findings from the Malaysian Elders Longitudinal Research study - Romli, Muhammad Hibatullah; Tan, Maw Pin; Mackenzie, Lynette; Lovarini, Meryl; Kamaruzzaman, Shahrul; Clemson, Lindy (Wiley-Blackwell, 2018)
Aim: Previous studies have investigated home hazards as a risk factor for falls without considering factors associated with the presence of home hazards. The present study aimed to determine patterns of home hazards among urban community-dwelling older Malaysians, and to identify factors contributing to home hazards. Methods: Cross-sectional data from the initial wave of the Malaysian Elders Longitudinal Research study were used. Basic demographics were obtained from the Global Questionnaire. Basic and instrumental activities of daily living were measured using the Katz and Lawton-Brody scales, and home hazards were identified using the Home Falls and Accidents Screening Tool. Participants were also asked if they had fallen in the previous 12 months. Results: Data were analyzed from 1489 participants. Hazards were frequently identified (>30%) in the toilet and bathroom areas (no grab rail, no non-slip mat, distant toilet), slippery floors, no bedside light access and inappropriate footwear. Lower educational attainment, traditional housing, Chinese ethnicity, greater number of home occupants, lower monthly expenditure, poor vision and younger age were the factors independently associated with home hazards. Conclusions: This study provides evidence that home hazards are a product of the interaction of the individual's function within their home environment. Hazards are also influenced by local sociocultural and environmental factors. The relationship between home hazards and falls appears complex and deserves further evaluation.